Professional Development through Story and Reflection: The Stepping Stones of Women in Leadership Program - Mary Dankoski; Julie Welch; Megan Palmer; Krista Hoffmann-Longtin; Emily Walvoord (Association of American Medical Colleges, 2014)
Abstract Despite the great strides made by women in medicine and science, they still comprise a small proportion of leadership roles in academic medicine. To students, residents, and the junior or midcareer woman faculty member, the path to leadership can appear confusing, complex, and riddled with challenges. Since self-reflection plays a powerful role in the development of women leaders in academic medicine, discussing life lessons of successful women can be an important method to empower women to create and embrace their own career paths. It was for the purpose of demystifying the path to leadership that this resource was developed. Through interviews conducted in front of an audience, this resource uses the power of successful women's stories to teach audience members about leadership and career development. Rather than a formal presentation, the interview format allows the personal and professional career development story to unfold more naturally, and capitalizes on the power of reflection to stimulate learning. This workshop is unique in that it uses public interviews with successful women leaders about their personal and professional milestones. We conducted this resource 17 times between 2008 and 2013, with a total combined attendance of 377 participants. At the conclusion of each interview, attendees were asked to evaluate the session. The session format was found to be highly interesting and effective, with a mean score of 4.67 on the Likert scale; individual session means on this item ranged from 4.28 to 5. Most attendees strongly agreed that they would recommend this program to others.